(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aimed to know the level knowledge of learning disabilities among a sample of class teacher students, and to know the weaknesses spots in their knowledge are known as learning disabilities, the researcher adopted the descriptive approach, the research sample consisted of (50) students, the researcher used a knowledge level scale prepared by Salman (2020), the results of the research showed that there is an average level of knowledge of learning disabilities among the sample of research, it was also found that the most prominent weaknesses in the knowledge of graduate students were about (the reasons learning disabilities, diagnosing learning disabilities, symptoms of academic learning disabilities).